Antioxidant Total and HOMA-IR of Diabetic Rats Given Crocatum piper and Andrographis paniculata Leaf Extracts - Nesti Rahmawati; Kusmiyati DK; Diana Nur Afifah (Faculty of Medicine, Diponegoro University, 2021)
Background: Type-2 diabetes mellitus (T2DM) is a silent killer which the prevalence continues to increase in every year. Increased oxidative stress occurs in T2DM. Red betel and bitter herb leaf extracts (RBBH) contain a lot of antioxidants. This combination is expected to provide better safety than if used singly because the content of andrographolid in bitter herb has effect such as nausea, vomiting, loss of appetite, and antifertility if consumed in high doses.Objective: The study aimed to prove the effect of red betel and bitter herb leaf extracts on antioxidant total and Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) in T2DM rats given high-fat diet and Streptozotocin (STZ) induction.Methods: Experimental randomized study with pre-post-test control group design using 25 Sprague Dawley male rats. T2DM model was conducted by providing high-fat feed for 14 days and induction of Streptozotocin-Nicotinamide, then given a combination of red betel and bitter herb leaf extracts at doses of 237.5 mg/kg BW, 225 mg/kg BW, and 212.5 mg/kg BW for 21 days. The measurement of antioxidant total used 2,2-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) method. HOMA-IR measured by ELISA (Enzyme-linked immunosorbent assay) method using insulin level equation and fasting blood glucose level measured by glucose oxidase-peroxidase aminoantrypirin (GOD-PAP). Data analysis used paired t-test, wilcoxon test, and ANOVA test to analyze differences in antioxidant total and HOMA-IR value among groups and followed by Bonferroni post-hoc test.Results: All treatments could reduce HOMA-IR and significantly increase antioxidant total (p<0.05). The most decrease in HOMA-IR and increase in antioxidant total at dose 237.5 mg/kg BW of red betel and bitter herb leaf extracts.Conclusion: The combination of red betel and bitter herb leaf extracts with dose 237.5 mg/kg BW, 225 mg/kg BW, and 212.5 mg/kg BW can improve blood glucose, insulin, and HOMA-IR levels in type-2 diabetes mellitus rats.